Development of augmented reality application for introducing tangible cultural heritages at the lampung museum using the multimedia development life cycle - Imam Ahmad; Yuri Rahmanto; Devin Pratama; Rohmat Indra Borman (Teknik Informatika Fakultas Ilmu Komputer Univeristas Muslim Indonesia, 2021)
Museum Lampung is one of the largest museums in Lampung Province which has a collection of tangible cultural heritage. If the museum visitors are seeking information about the collections, they will be assisted by museum guides orally. However, the limited number of guides are not enough to serve visitors during the school holidays. Therefore, to help visitors to find information about its cultural heritage collection, Augmented Reality (AR) technology was developed. AR is a technology that can display 3D objects in a real environment. The AR application that will be built is developed with the MDLC approach, where this method is suitable for developing multimedia applications. This research produces an application that can display 3D objects when the user's camera is directed to the collections of Museum Lampung and provides information related to these objects. Based on the test results on aspects of perceived usefulness, convenience, intention, and user friendliness, generally respondents answered